Adsorption And Regeneration Of Sungai Pasak Pumice As An Adsorbent For Ammonium Removal In Water - Ningsih Ika Pratiwi; Annisa Huwaida; Shinta Indah; Denny Helard (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2019)
Pumice is known as a low-cost material with a porous structure, has the potential as an adsorbent to remove various kinds of pollutant compounds. The abundance of pumice is found in Sungai Pasak area and it never been utilized. This study was performed to see the ability of Sungai Pasak pumice as an adsorbent for ammonium removal in water along with its ability to be regenerated. The study was carried out triplo in batches to obtain optimum adsorption conditions which were then used in desorption experiments using HCl 0.1 M agent for regeneration process. The optimum conditions obtained: adsorbate pH 6, adsorbent dose 0.3 g/l, contact time 30 minutes, adsorbent diameter <63 µm and adsorbate concentration 4 mg/l. The results showed that pumice has ability to remove ammonium with adsorption capacity at optimum conditions were 47.06% and 6.27 mg/g with Freundlich's isotherm equation (R2=0.997). Acid agents are able to adsorb ammonium from pumice with an average desorption percentage 88.89% after 2 times of reuse, proving that acidic agents are able to regenerate pumice adsorbents so they can be reused. The potential for adsorption and regeneration of the Sungai Pasak pumice can be utilized to treat water with ammonium such as groundwater and waste water.